Effect of Moisture Content and Variety on the Some Physical and Aerodynamic Properties of Sesame Seeds Relevant to Its Processing. - Eze, Paul Chukwuka; Eze, Chikaodili Nkechi; Ide, Patrick Ejike (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
The physical and aerodynamic properties of black and white sesame were determined at Moisture Content(MC%) range of 8.5 – 30.6%(d.b).The major, minor, intermediate, arithmetic mean, geometric mean diameters and sphericity, projected area of the two varieties were 2.96 – 3.94mm, 1.47 -2.40mm,0.54 -1.26mm,1.66 – 2.50mm, 0.78 - 3.66mm and 26.53 – 93.45, 1.91 – 42.08mm2 respectively.The increase in MC resulted decrease in true density from 1038.61 – 994.93 kg/mm2 and 1039.61 – 998.47 kg/mm2 for white and black sesame seed respectively.The terminal velocity of white sesame seed ranged from 3.12 – 7.82m/s while black sesame seed ranged from 3.16 – 7.94m/s at MC range of 8.5 – 306% (d.b).The drag coefficient were 3.750.31 and 2.26 – 0.23 for white and black sesame seed respectively as MC ranged from 8.5 – 30.6% (d.b) while Reynold number varied from 2363.9 – 23067.3 and 3401.5 – 15121.6 for white and black sesame seed respectively at MC range of 8.5 - 30.6% (d.b).The properties of sesame seed determined varied significantly with variety and MC.This findings are the prerequisite in the design and selection of sesame seed separating machine. A pneumatic separator can be designed with provision for effective separation of undesired light material with average terminal velocity below 5.17m/s and 5.67m/s for white and black sesame seeds respectively.